RUMAH TRADISIONAL JOGLO DALAM ESTETIKA TRADISI JAWA - Slamet Subiyantoro (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
Javanese traditional house has its own aesthetics value which represents the manifestation of the Javanese’s way of life in response to the environment. Joglo as a building is a symbolic representation of reality whose values has exceeded the form and the structure  of the building.  Joglo  in its Javanese  language  means to establish communication  with the God either vertically or horizontally with other nature and environment